I am where I believe my body is: The interplay between body spatial prediction and body ownership. - Francesca Frisco; Vito Bruno; Daniele Romano; Giorgia Tosi (PLoS ONE)
Body ownership refers to the feeling that the body belongs to oneself. This study explores how our ability to predict our body's location in space influences feelings of ownership and disownership towards it, comparing two illusion techniques: the virtual Rubber Hand Illusion (vRHI) and the first-person perspective Full-Body Illusion (1pp-FBI). Participants were exposed to each illusion, where they observed a virtual body aligned or misaligned with their own. Participants observed the virtual body for 60s (i.e., visual exposure) and then experienced the multisensory body illusion. During the illusion, participants received tactile stimulation while observing the avatar being synchronously touched. After two minutes, a virtual knife appeared and stabbed the virtual body. We recorded the Skin Conductance Response (SCR) as an implicit embodiment measure. After the visual exposure and the body illusion, we administered a Body Localization Task to evaluate the body's perceived position and a questionnaire to measure embodiment and disembodiment subjective experience. We performed a series of Bayesian regression in a factorial within-subject design. Results showed that both illusions increased feelings of ownership, but this effect was weaker in the misaligned 1pp-FBI. Interestingly, disownership only occurred in the misaligned 1pp-FBI, particularly when the legs were misaligned. Additionally, we found a recalibration of the body's position toward the misaligned virtual body, but no changes emerged when the real and the fake body were aligned. Correlation analyses partially supported the hypothesis that the perceived body's position influences embodiment sensations in the 1pp-FBI. These findings suggest that our perception of where our body is in space plays a crucial role in how much we feel it belongs to us, supporting the idea that ownership may be more related to the perceived location than the body itself.